A survey of methods used for source localization using EEG signals - Jatoi, Munsif Ali (2014)
tThe EEG source localization which is used to localize the electrical activity of brain has been an activearea of research as it provides useful information for study of brain’s physiological, mental and functionalabnormalities. This problem is called EEG inverse problem. The localization of the active sources needs thesolution of ill posed EEG inverse problem. Since the foundation of this field till today, many methods havebeen developed with the aim of in-depth localization, high resolution, reduction in localization/energyerror and decreased computational time. In this survey, EEG inverse problem is discussed with its primaryto most developed and recent solutions. The introduction to the field along with the categorization of dif-ferent solutions is provided. Also, the relative advantages and limitations for each method are discussed.Finally, the challenges and future recommendations are provided, in the end, for further improvementof EEG inverse problem in terms of resolution, computational power and localization error.